High-Frequency Vacuum Electron Devices - Feng, Jinjun; Gong, Yubin; Du, Chaohai; Cross, Adrian (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Vacuum electron devices at frequencies of millimeter waves and terahertz play highly important roles in the modern high-data rate and broadband communication systems, high-resolution detection and imaging, medical diagnostics, magnetically confined nuclear fusion, etc. For the fast motion velocity of electrons in the vacuum medium, they have the advantages of high power and high efficiency, as well as compactness, compared with other present radiation sources, such as solid-state devices.We established the Special Issue of "High-Frequency Vacuum Electron Devices" with the aim of enhancing the exchange of research information on the theory, design, simulation, processes, and development of these devices to promote their applications, and to attract young researchers and engineers starting out in this important field, which is still vital on the basis of modern electronic science and information technology.